Dhvanyālokaḥ - Anandawardhana (Śrīkuppusvāmiśāstri Risarca Insṭiṭut dvāra prakāśiṭah, 1944)
Classical work, with Locana of Abhinavagupta and Kaumudī of Udaya, 16th cent. on Sanskrit poetics
Includes indexes
Keywords: Sanskrit poetry; Poetics; Dhvani (Poetics)